Pituitary function through the ages - Ross, Richard J. M; Erfurth, Eva Marie (BioScientifica, 2004)
A collection of papers presented at a symposium that focused on the function of the pituitary hormone and on growth hormone replacement therapy. Intended for professional public.
HypoCCS series, ISSN 1466-4151 volume 8
Keywords: Hormone Replacement Therapy; hormonální substituční terapie; endokrinologie; Growth Hormone; růstový hormon